2022-RA-1061-ESGO Paget's disease of the nipple. (20th October 2022) - Saoud, Mohammed Karam; Taghzouti, Hanae
Abstract : Introduction: Paget's disease of the nipple corresponds to the infiltration of the nipple-areolar complex by tumor cells. It is a rare condition that can be either isolated or associated, most often, with a homolateral breast cancer. Clinically, it presents as an eczematous rash with an erythematous, exudative or scaly, well-demarcated, slightly infiltrated area, which the patient often describes as a burn on the nipple and areola. The interest of imaging based on echomammography and breast MRI is therefore to look for an underlying cancer. The diagnosis of Paget's disease is made either by cytological scraping of the nipple or, at best, by nipple-areolar biopsy. Its management is conditioned by the presence or not of an underlying breast cancer. Methodology: Five cases of STUMP treated in the department of gynecology-obstetrics I at the CHU Hassan II in Fez between 2018 and 2021 were analyzed retrospectively. Results: Of the 05 patients, we had isolated paget in 1 case, and i twas associated with breast carcinoma in 4 cases All patients had surgical treatment. Anatomopathological analysis of the surgical specimens revealed paget disease of the nipple in all cases. Conclusion: It's important to know the clinical presentation of Paget's disease of the nipple, as well as the interest of imaging and anathomopathological study in the diagnosis of these lesions. To finally define the principles of therapeutic management.